Independent Variables for Determining the Cumulative Live Birth Rates of Aged Patients with Polycystic Ovary Syndrome or Tubal Factor Infertility: A Retrospective Cohort Study - Guan, Yichun; Kong, Pingping; Xiao, Zhiying; Zhang, Junyan; He, Jingfang; Geng, Wenjun; Yan, Junfang; Sun, Simin; Mu, Mingkun; Du, Xiaofang; Wang, Xingling (Frontiers in Endocrinology, 2022)
Objective: To assess whether women of advanced age (≥35 years) with polycystic ovary syndrome (PCOS) have the same cumulative live birth rate (CLBR) as their age-matched controls with tubal factor infertility and to determine the influencing factors on the CLBRs of aged women. Design: A retrospective cohort study. Setting & population: A total of 160 women of advanced age (≥35 years) with PCOS and 1073 women with tubal factor infertility were included in our study. All patients underwent their first fresh cycles and subsequent frozen cycles within in one year in our centre from 2015 to 2020. Methods: To determine independent influencing factors on the CLBRs of these aged patients, a multivariable Cox regression model of CLBR according to the transfer cycle type was constructed. Main outcome measure(s): CLBRs. Result(s): The Cox regression model of the CLBRs indicated that there was no significant difference between the PCOS group and the tubal infertility group in terms of advanced age (HR, 0.95; 95% CI, 0.71-1.27, P=0.732). The CLBR significantly decreased for women of advanced reproductive age up to 37 years of age (HR, 0.46; 95% CI, 0.39-0.56, P<0.001). The CLBR increased by 63% when more than ten oocytes were retrieved (HR, 1.63; 95% CI, 1.34-1.98, P<0.001). Patients with an AMH level above 32.13pmol/l were likely to have a 72%（HR, 1.72; 95% CI, 1.08-2.73, =0.023） and 34% （HR, 1.34; 95% CI, 1.07-1.68, P=0.010）improvement in CLBR compared to those with an AMH below 7.85pmol/l and 7.85-32.12pmol/l, respectively. Conclusion(s): Despite the higher number of oocytes retrieved in PCOS patients, the reproductive window is not extended for PCOS patients compared with tubal factor infertility patients. Age, AMH and the number of oocytes retrieved play crucial roles in the CLBRs of patients of advanced age (≥35 years).